Diagnóstico das classes hospitalares no Estado de Minas Gerais: atendimento educacional por um fio - Jacqueline Luiz Leite Dantas (2023)
During the hospitalization process, children and adolescents are deprived of contact with friends, limited in their actions and unable to carry out several activities, including attending school. The hospital educational service, named by the Ministry of Education as Hospital Class (HC), is configured as an alternative for schooling sick students, outside the common environment. This research had as its general goal to understand how the existing HC in the state of Minas Gerais are structured and how they work. The study is situated in the field of Special Education and Public Policies on Inclusive Education, where the trajectory of the sick student is linked. To accomplish that, the development of a study with an exploratory nature and a qualitative approach study was proposed. The methodological proceedings used were the bibliographic review, document analysis and data collection on the HC operating in the state. Professionals that work on the HC were invited to answer a questionnaire and to participate in two focus groups. The data collected from the questionnaires were organized and, subsequently, crossed with the current legislation and the theoretical framework. Data from the focus groups were analyzed using the Discourse of the Collective Subject (DCS) software. Three different contexts were investigated: the historical, which retrieved information about the first hospital classes in the state of Minas Gerais; the political, that analyzed the legal frameworks that supply the guidelines for the implementation of public policies for the educational inclusion of the student undergoing health treatment; and the geographical/institutional, that identified the HC in the different regions of the state and its institutional connections. The results showed that, in relation to historical aspects, there were hospital classes linked to the State Department of Education (SDE) between the 1940s and 1990s, with the oldest record being that of the Combined Schools attached to the Benjamin Guimarães Foundation, which today is Hospital of Baleia. With regards to the legal aspects, it became evident that the hospitalized student is at times considered Special Education public, and at other times loses this status, remaining in limbo. The lack of definition of the place this student occupies in the legislation makes the offer of hospital classes services precarious and makes it impossible for this student to access Basic Education with equity. Finally, the geographic/institutional context allowed the identification of 16 hospital classes operating in the state, which enabled the construction of a state register and points to a predominance of classes linked to the health system/hospitals and not to the education secretariats. Finally, the analysis of the questionnaires and the focus groups enabled the construction of the predominant service profile in the state. It is concluded that the offer of educational assistance is still very restricted and, consequently, does not guarantee this right to all students. The research opens space to foster dialogues regarding the educational right of hospitalized students and offers elements to encourage the construction of public policies aimed at this specific public.